Synthesis, Characterization and Analytical Applications of A New Ion Exchange Material Based on Antimony(III) - Chand, Subhash; Seema; Arti; Vijay Chahal, Chandra (Asian Journal of Chemistry, 2011)
Antimony based inorganic cation exchanger [antimony(III) molybdosilicate] has been synthesized. It has been characterized using XRD, I.R., TGA studies in addition to its ion exchange capacity, pH titration, chemical stability, thermal stability and distribution behaviour. The ion exchange capacity of the synthesized ion exchanger in H+ form is found to be satisfactory. Ion exchange capacity has also been determined for various metal ions such as K+, Mg2+, etc., pH titration method was also used for the determination of ion exchange capacity. Kd values have also been determined for ten different metal ions. The exchanger is found to be selective for Pb2+. Ion exchanger column was used for binary separation and water softening.